2021
DOI: 10.1051/parasite/2021003
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of insecticide resistance in Anopheles coluzzii populations in the city of Yaoundé, Cameroon and influence on pyrethroid-only treated bed net efficacy

Abstract: In Cameroon, pyrethroid-only long-lasting insecticidal nets (LLINs) are still largely used for malaria control. The present study assessed the efficacy of such LLINs against a multiple-resistant population of the major malaria vector, Anopheles coluzzii, in the city of Yaoundé via a cone bioassay and release-recapture experimental hut trial. Susceptibility of field mosquitoes in Yaoundé to pyrethroids, DDT, carbamates and organophosphate insecticides was investigated using World Health Organization (WHO) bioas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Many studies reported escalation in resistance to pyrethroids across the country in An. coluzzii [ 29 , 41 ] and An. funestus [ 42 ] but it is the first time resistance have been noticed for organophosphates.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported escalation in resistance to pyrethroids across the country in An. coluzzii [ 29 , 41 ] and An. funestus [ 42 ] but it is the first time resistance have been noticed for organophosphates.…”
Section: Discussionmentioning
confidence: 99%
“…Other means of protection, such as insecticide sprays, mosquito coils and screens on windows were also used by the population. Previous studies have shown that the use of insecticide sprays, especially in purely agricultural areas, would increase the rate of resistance in the mosquito population [ 4 , 28 , 46 ] and would, therefore, reduce the bio-efficacy of LLINs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional expression analysis in An. gambiae indicated that Cyp9k1 was able to metabolize deltamethrin, as well as pyriproxyfen [ 39 , 40 ]. Cyp6p4, Cyp6z1, Cyp6p3 and Cyp6m2 were also found to be upregulated in at least one population.…”
Section: Discussionmentioning
confidence: 99%
“…Cyp6p4, Cyp6z1, Cyp6p3 and Cyp6m2 were also found to be upregulated in at least one population. Cyp6p4, Cyp6m2 and Cyp6p3 have been shown to metabolize pyrethroids (permethrin, etofenprox, deltamethrin) [ 36 , 37 , 39 ]. Cyp6z1 have been reported to metabolize DDT in An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation